Riqueza y composición de arañas en diferentes coberturas vegetales del Parque Natural Regional el Vínculo (Valle del Cauca, Colombia) (2010)
This study aimed to estimate the spider species richness at Parque Natural Regional El Vínculo (Valle del Cauca, Colombia). We sampled spiders during day and night sessions from August to December 2008 in five vegetation types: secondary forest, riparian forest, shrubs, grassland and highly disturbed area. We used aerial and ground hand collection, beating, sorting litter and pitfall traps. We used the non-parametric richness estimators ACE, ICE, Chao 1, Chao 2, first-order Jackknife and second-order Jackknife in order to calculate the average species richness. Additionally, we calculated the average sampling efficiency. A total of 1565 adult specimen, representing 36 families and 193 morphospecies in 238 sampling units were found. The average estimated richness ranged from 46 (shrubs) to 101 (secondary forest) morphospecies. The values of average sampling efficiency ranged from 70% (secondary forest) to 90% (shrubs). The average estimated richness for the natural park was 238 morphospecies and the average sampling efficiency was 81%. Our results increases the number of families registered in the park in 14 and suggest this location as the place with more families of spiders in the Valle del Cauca.